Reframing high street viability: A review and synthesis in the English context. (March 2023) - Ntounis, Nikos; Saga, Regine Sønderland; Warnaby, Gary; Loroño-Leturiondo, Maria; Parker, Cathy
Abstract: Changing consumer trends, waves of retail decentralisation, and various socio-economic and environmental shocks have exacerbated the well-recognised challenges of retail-dominant English high streets in recent years. The decline and 'death' of the high street has been the subject of many policy responses aiming at transforming high streets as viable multifunctional hubs and local community anchors. However, this vision implies a narrative change of high street viability beyond established economic and property-oriented interpretations, which is presently unclear in conceptual and operational terms. This paper identifies the conceptual ambiguities and tensions evident in English policy and reframes high street viability at the confluence of other 'loose concepts' (sustainability, resilience, adaptability, liveability). Through a scoping review, this paper synthesises studies discussing these interrelated concepts, and presents their development since the influential URBED Vital and Viable Town Centres report. We argue that the factors contributing to the interrelated concepts form a joint effort towards achieving high street viability, but can also be distinguished by temporal variations and areas of concentration. Highlights: A renewed interest in high street viability necessitates a reframing of the concept We address the conceptual and operational ambiguity of high street viability in English policies over the past 30 years We illustrate the confluence of viability in relation to sustainability, resilience, liveability and adaptability High street viability is a dynamic concept that corresponds to the long-term, changing challenges and needs of communities